The 35,2 kda Hemaglutinin Protein of Pili’s Proteus mirabilis P355 as Adhesin on Rabbit’s Blader Epitelial - Diana Chusna Mufida; Enny Suswati (Jurnal ILMU DASAR, 2007)
Urinary tract infection represent one of nosocomial infection in hospital. One of agent nosocomial urinary tract infection is Proteus mirabilis bacteria and common occur on patient with urinary catheter. Urinary tract infection with caused by P. mirabilis was persistent, very difficult to eradicated. Further more is caused some complication such as cystitis, acut and cronic pyelonephritis, kidney bladder stone, bacterimiae and sepsis. This bacteriae has same virulence factors. Fimbriae is one of it. In the adhesion test utilization of protein hemaglutinin pili 35.2 kDa resulted in the electroelusion which salluted in vesica urinaria epitelial by dose 400μl , 200μl, 100μl, 50μl, 25μl, 12,5μl and 0μl as control. Form adhesion test on vesica urinary epitelial that salluted with 35.2kDa protein pili we faund that the higher dose of protein can decrease bacteriae consentration at vesica urinary epitelial. This result was significant with r= 0.93 and p value = 0.005. This conclusion of this study is 35.2 kDa molecular weight protein pili of P. mirabilis P355 were adhesion protein.Keywords : hemaglutinin, pili, Proteus mirabilis, adhesin